Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Solve the following linear equations. m – (m - 1)/2 = 1 – (m - 2)/3

Solve the following linear equations. 
m – (m - 1)/2 = 1 – (m - 2)/3 

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5870 Points
3 months ago
Dear Student

m–(m-1)/2=1–(m-2)/3
⇒m–m/2–1/2=1–(m/3–2/3)
⇒m–m/2+1⁄2=1–m/3+2/3
⇒m–m/2 + m/3 = 1 + 2/3–1⁄2
⇒m/2+m/3=1⁄2+2/3
⇒(3m+2m)/6=(3+4)/6
⇒5m/6=7/6
⇒m=7/6×6/5
⇒m=7/5

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free